Penggunaan Pola Kalimat Kagiri dan Kagiri DA dalam Bahasa Jepang (Analisis Struktur dan Makna) - Putri, Mellati Riandi; Wagiati, Wagiati (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2021)
The purpose of this research is to find the way of using kagiri and kagiri da as sentence patterns in Japanese. The type of this research is qualitative research with descriptive method. The data was taken from Japanese online news website, Asahi Shinbun which published on early December 2020 that contain sentences that using kagiri and kagiri da sentence pattern. There are 21 data gathered from Asahi Shinbun, and based on the part of speech that formed with kagiri and kagiri da sentence pattern, there are ten data were classified as noun, nine data were classified as verb, and 2 data classified as adjective. The kagiri sentence pattern used as conjunction when formed with noun and verd with semantic meaning as “while” with certain condition or terms, and used as suffix when formed with noun which containing number or time with semantic meaning of limitation of something. While the kagiri da sentence pattern only formed with adjectives and always in the end of the sentence with semantic meaning of describing a certain level of the speaker feelings. The kagiri sentence pattern have a lot of variations such as formed with joshi in ni kagiri pattern, ni kagitte pattern, and ni kagiru pattern. The further research through another data source such as corpus may needed to find another purpose of this sentence pattern. Keywords: syntax, semantic, verb, kagiri, kagiri da